اقتصاد الظل, أسبابه, آثاره السلبية وأساليب الحد من حجمه / مثال سورية / - الحسن, علي حسين (Latakia University Journal - Economic and Legal Sciences Series, 2014)
إن ظاهرة اقتصاد الظل تمثل انحرافا"عن الاقتصاد الوطني في معظم الدول حيث يشكل اقتصاد الظل معدلات عالية من الناتج القومي لهذه الدول , وهو يشمل الأنشطة الاقتصادية كافةالتي يمارسها الأفراد والشركات ولم تسجل بشكل رسمي ولا تدخل في حسابات الدخل القومي ولا تخضع للنظام الإداري والقانوني, مما يؤدي إلى تضليل في الإحصائيات والمعلومات ومما يجعلها غير دقيقة ولا توضح الإمكانيات الحقيقية للدولة والتي بدورها تؤدي إلى سوء توزيع الموارد الاقتصادية والناتج القومي . هذا البحث يهدف إلى دراسة أسباب هذه الظاهرة وطرق تحييدها ومعالجتها في سورية. The phenomenon of the shadow economy represents a threat to the national economy in most countries because it is high rates of gross national product., Which includes all economic activities practiced by individuals or companies have been not recorded officially and not intervened in the national income accounts also it not subject to the administrative and legal systems , it will leads to mislead in statistics and information and making it inaccurate and shows not true potential of the state, which in turn lead to the misallocation of economic resources and the gross national product. This research aims to study the causes of this phenomenon and ways of tackling them in Syria.